Identification of Meloidogyne panyuensis (Nematoda: Meloidogynidae) infecting Orah (Citrus reticulata Blanco) and its impact on rhizosphere microbial dynamics: Guangxi, China - Zhang,Xiaoxiao; Zhao,Wei; Lin,Yuming; Shan,Bin; Yang,Shanshan (PeerJ, 2024)
Root-knot nematode disease severely affects the yield and quality of the mandarin variety Citrus reticulata Blanco “Orah” in Guangxi, China. Nevertheless, the pathogen and the effects of this disease on microbial communities remain inadequately understood. This study identified the root-knot nematode Meloidogyne panyuensis in the rhizosphere of infected Orah using morphological and molecular biological methods. Soil chemical properties indicated that organic matter, total nitrogen (TN), total phosphorus (TP), available phosphorus (AP), total potassium (TK), and available potassium (AK) were significantly higher in the rhizosphere soil of M. panyuensis-infected Orah than in that of healthy plants. The relative abundance of the bacteria Bacillus, Sphingomonas, and Burkholderia-Caballeronia-Paraburkholderia, as well as the fungi Lycoperdon, Fusarium, Neocosmospora, Talaromyces, and Tetragoniomyces, was elevated in the rhizosphere soil of M. panyuensis-infected plants. Furthermore, organic matter, TN, available nitrogen (AN), TP, AP, TK, and AK exhibited positive correlationswith these bacteria and fungi in the rhizosphere soil of M. panyuensis-infected Orah. Potential biocontrol strains, such as Burkholderia spp., were identified by comparing the differences in rhizosphere microbial composition between healthy Orah and M. panyuensis-infected Orah. Our findings provide a foundation for the early warning and prevention of root-knot nematode disease in Orah.
Keywords: Citrus reticulata Blanco; Root-knot nematode; Meloidogyne panyuensis; Rhizosphere soil; Microbiome